Variability in individual musculoskeletal response is not increased by countermeasures during bed rest - Böcker, Jonas; Schmitz, Marie-Therese; Hoffmann, Leona; Bloch, Wilhelm; Rittweger, Jörn (Frontiers in Physiology, 2025)
IntroductionUnder weightlessness conditions, there is a loss of bone and muscle mass. However, these adaptations are subject to great inter-individual variability. As an analogue to weightlessness, bed rest studies are carried out on Earth, which also serve to test countermeasures counteracting bone and muscle loss. Since study participants react differently to any interventions such as countermeasures, it can be assumed from a statistical point of view that the between-subject variation (BSV) is inflated when combining bed rest with countermeasure exercises. The aim of this study was therefore to examine whether a countermeasure has an effect on the magnitude of BSV. MethodsTo this purpose, the decrease in muscle cross-sectional area and bone mineral content was analyzed at different measurement sites of 123 subjects in the control and intervention groups from six bed rest studies that tested different countermeasures. A novel statistical approach was chosen enabling quantification of the specific amount of variability after countermeasures (UCM). ResultsThe comparison of the observed variability (UObs) between intervention and control groups showed no difference (all p ≥ 0.08), suggesting that BSV was not affected by the countermeasures. UCM was negligible in the context of the overall variability, indicating that it plays a subordinate role in whether a crew member responds weakly or strongly to a training intervention. ConclusionBut rather, the extent to which, the astronaut reacts to unloading is the main factor influencing variability.